Big Five personality traits and coping strategies of Italian university students during the COVID-19 pandemic first wave - Burro, Roberto; Vicentini, Giada; Raccanello, Daniela (Frontiers in Psychology, 2023)
Little is known about the role personality traits may have played for university students in diminishing and compensating for the negative impact of COVID-19 in its early phases, promoting adaptive coping. University students represent a population which was consistently obliged to follow social distance rules due to the early shift of many organizations from face-to-face to online learning. Therefore, it is worth exploring whether the Big Five traits acted as risk or protective factors after the outbreak of a disaster such as the COVID-19 pandemic for Italian university students. We involved a sample of 2995 university students who completed an online survey in March 2020. We measured the Big Five personality traits through the Big Five Inventory-2-XS (Soto and John, 2017) and their coping strategies through the Robust – Pandemic Coping Scale (Burro et al., 2021). The latter assessed four COVID-19-related coping dimensions, namely Despair (e.g., including helplessness and feeling lack of control), Aversion (e.g., referring to oppositive strategies), Proactivity (e.g., comprising problem solving and information seeking), and Adjustment (e.g., concerning reappraisal and assertiveness). Preliminarily, two Linear Mixed Models indicated that university students had higher scores in Conscientiousness, followed by Open-Mindedness, and then Agreeableness. These three traits were, in turn, higher than Extraversion and Negative Emotionality, which did not differ among them. Concerning coping, university students reacted more frequently utilizing adaptive strategies (with Proactivity used more frequently than Adjustment) rather than maladaptive strategies (with Despair higher than Aversion). A Path Analysis examining the relations between the Big Five traits and the four coping dimensions showed that Negative Emotionality can be considered as a risk factor, and that Agreeableness, Conscientiousness, and Open-Mindedness can be conceptualized as protective factors. More interestingly, we found that Extraversion entailed both a risk and a protective role for Italian university students after the outbreak of the COVID-19 pandemic. Notwithstanding limitations, these findings can be the basis for developing disaster preparation and prevention actions, aiming at promoting students’ positive coping towards current and future disasters.